Use of internet resourсes during lessons - Ziyayeva Kamola Ziyaiddinovna (Research Parks Publishing LLC, 2020)
Тhe study of foreign languages plays an important role in the modern world. This article explores the use of Internet resources during English lessons, as well as working with information and communication technologies (ICT) and the use of multimedia teaching methods. Therefore, it is so important to improve the method of using computer information technologies in teaching English